INTEGRATING MACHINE LEARNING AND SMART TECHNOLOGIES IN EDUCATION: A SYNERGISTIC APPROACH FOR ENHANCED LEARNING OUTCOMES - Sagi Moldakyn; Vassiliy Serbin (Reviews of Modern Science, 2024)
This article explores the potential of combining Machine Learning (ML) and SMART (Specific, Measurable, Achievable, Relevant, Time-bound) technologies to revolutionize the educational landscape. By leveraging the strengths of ML for data-driven insights and SMART principles for goal-oriented learning, we propose a framework that promises to enhance the effectiveness, efficiency, and personalization of educational experiences. The article discusses the theoretical underpinnings, practical implementation, and potential benefits of this integrated approach.